(untitled) (Bulletin KNOB, 2015)
In Flanders, large-scale exploitation of the landscape was initiated in the tenth century by abbeys and by powerful landowners like the Count of Flanders. As a consequence, a lot of forested areas were converted into arable land and the remaining forest and woodlands became highly fragmented. It is estimated that in Flanders the lowest forest cover ever was reached by the end of the thirteenth century. It is known that from the thirteenth century onwards, Flemish towns imported massive amounts of construction timber. However, the wholesale depletion of local forests and the associated timber supply is contradicted by many archaeological discoveries of wooden structures built from local material. The provenance of such historical timbers can be determined by tree-ring analysis. Most probably, scarcity was not the sole factor behind the large-scale importation of construction timber. Quality, or rather the lack of high quality-timber on the local market, must also have played a role. During the Middle Ages the practices of coppicing and coppicing with standards were widely applied. These types ofwoodland management are highly productive and make it possible to harvest firewood and small-sized lumber in a relatively short time. However, these management practices are not best suited to the production of large quantities of straight-grained and high-quality construction timber. Due to the lack of large quantities of high-quality local timber, the importation of construction timber became increasingly important. An examination of the fourteenth and fifteenth century municipal accounts of several Flemish cities reveals that at least three major source regions can be identified for the timber imported into Flanders: the Baltic harbours and Scandinavia in the north, the forests along the Rhine, and the Ardennes and Meuse regions in what is now southern Belgium. Dendrochronological research into roof constructions in Bruges, Ghent and Oudenaarde demonstrates that the timbers were often imported from forested regions along the River Meuse. The trees were felled, tied together to form a raft and floated downriver to the coast. Eventually, most of these rafts arrived at the timber market in Dordrecht, from where they were shipped to Damme, the port for Bruges. In the Bruges municipal accounts, the town of Dordrecht is frequently cited as the place where timber was purchased for civil construction projects. This timber was also in demand further inland where it was used for large roof constructions. Although it is known that Baltic oak was imported, such timbers were never used for construction, but for more delicate applications such as panelling, staves or sculptures. A constant feature of medieval wood construction in Flanders is the use of oak, with only a few known examples of elm being used instead. Coniferous wood, although mentioned in the municipal accounts, was rarely used in historical wooden construction in Flanders. During the Middle Ages, widespread human intervention in local forests (timber harvesting, conversion to farmland), left them highly fragmented. While still able to produce everyday construction timber, local forests were no longer able to meet the ever-growing demand for high-quality construction timber.